The Effect of Work Stress and Work Conflict on Employee Performance at the Regional Mental Hospital of Lampung Province - Helga Eva Virginia; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2025)
his study aims to analyze the impact of Work Stress and Work Conflict on Employee Performance at the Regional Mental Hospital of Lampung Province. Existing research on work-related stress and conflict in healthcare settings has highlighted their potential adverse effects on performance, but limited studies focus on mental health institutions in this region. A descriptive quantitative approach was employed, with data collected from 76 respondents using convenience sampling and the Slovin formula. Data analysis was conducted through multiple linear regression, revealing that Work Stress and Work Conflict explain 51.5% of the variation in Employee Performance, as indicated by an R-squared value of 0.515. The remaining 48.5% of Employee Performance is influenced by other unexamined factors such as workload, commitment, and compensation. The findings demonstrate that Work Stress and Work Conflict significantly affect Employee Performance, contributing novel insights into the factors influencing employee outcomes in mental health hospitals and offering a better understanding of how these elements can be managed to enhance performance.